Etika Komunikasi Penyiar Radio: Implementasi Etika Komunikasi Islam Penyiar Radio MQ 92.3 FM Yogyakarta - Arif Nurrokhim (FAI, 2017)
Etika Komunikasi Penyiar Radio: Implementasi Etika Komunikasi Islam Penyiar Radio MQ 92.3 FM Yogyakarta